2020
DOI: 10.3390/s20071881
|View full text |Cite
|
Sign up to set email alerts
|

PEDOT:PSS-Based Conductive Textiles and Their Applications

Abstract: The conductive polymer complex poly (3,4-ethylene dioxythiophene):polystyrene sulfonate (PEDOT:PSS) is the most explored conductive polymer for conductive textiles applications. Since PEDOT:PSS is readily available in water dispersion form, it is convenient for roll-to-roll processing which is compatible with the current textile processing applications. In this work, we have made a comprehensive review on the PEDOT:PSS-based conductive textiles, methods of application onto textiles and their applications. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
116
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 160 publications
(117 citation statements)
references
References 107 publications
1
116
0
Order By: Relevance
“…Silver-nanoparticle ink edges over copper nanoparticles due to their low rate of oxide formation [ 21 ]. Very few investigations have been observed for flexible antennas based on copper-based nanoparticles [ 22 ]. Besides nanoparticles, electro-textile materials like Ni/Ag-plated, Flectron (copper-coated nylon fabric), and nonwoven conductive fabrics (NWCFs) are generally used in flexible antennas.…”
Section: Materials For Flexible Antennasmentioning
confidence: 99%
“…Silver-nanoparticle ink edges over copper nanoparticles due to their low rate of oxide formation [ 21 ]. Very few investigations have been observed for flexible antennas based on copper-based nanoparticles [ 22 ]. Besides nanoparticles, electro-textile materials like Ni/Ag-plated, Flectron (copper-coated nylon fabric), and nonwoven conductive fabrics (NWCFs) are generally used in flexible antennas.…”
Section: Materials For Flexible Antennasmentioning
confidence: 99%
“…In this work, we have added polydimethylsiloxane-b-polyethylene oxide (PDMS) which compensates for the stiffness from PEDOT:PSS. Moreover, we have utilized a different conductive polymer composite of PEDOT:PSS, because of its acceptable electrical conductivity and flexibility [8,9], and PDMS, due to its biocompatibility and extensibility [10]. The result should be a single fabric that senses both strain and moisture.…”
Section: Introductionmentioning
confidence: 99%
“…PEDOT:PSS is attractive because of its high optical transparency, electrical conductivity, mechanical durability, electrochemical performance, and compatibility with roll-to-roll (R2R) processing. [15,22] It has been reported that the optoelectronic properties of PEDOT:PSS TCEs can be further enhanced by incorporating Ag metal mesh/stripes, giving rise to better device performance in organic devices, such as OSCs, organic light-emitting diodes, and even SCs. Moreover, the PEDOT:PSS/Ag hybrid TCE can produce more efficient stripe-shaped devices due to the underlying Ag sub-metal electrodes.…”
Section: Introductionmentioning
confidence: 99%